Diskursus Rasisme pada Stratafikasi Status Sosial dalam Perspektif Komunikasi Antar Budaya - Teguh Hidayatul Rachmad; Yohanes Probo Dwi Sasongko (Journal of Communication Research, 2025)
Keberagaman budaya dan agama yang ada pada masyarakat Indonesia menuntut adanya toleransi antar umat beragama yang semakin penting untuk diperkuat. Dalam konteks ini, lembaga pendidikan agama seperti pesantren memiliki peran strategis dalam menanamkan nilai-nilai toleransi. Artikel ini membahas peran Pesantren Sunan Kalijogo Malang dalam mengajarkan nilai-nilai toleransi beragama di tengah masyarakat yang penuh dengan keberagaman. Fokus utama kajian ini adalah pada strategi pesantren mengimplementasikan ajaran Islam yang menekankan pentingnya saling menghargai perbedaan dan hidup berdampingan secara damai. Penelitian ini berusaha untuk menggali motivasi pesantren dalam mengajarkan toleransi, serta metode yang digunakan untuk menanamkan nilai-nilai tersebut kepada santri. Menggunakan pendekatan kualitatif, data dikumpulkan melalui observasi lapangan, wawancara mendalam. Strategi ini dilakukan oleh pihak pesantren tidak hanya memberikan pendidikan agama Islam, tetapi juga menciptakan ruang bagi santri untuk memahami dan menerima keberagaman dalam kehidupan sosial mereka. Implementasi komunikasi multikultural di pesantren ini membuktikan bahwa lembaga pendidikan agama dapat berperan penting dalam menciptakan santri yang inklusif dan toleran, serta menjaga keharmonisan di tengah masyarakat yang multikultural. Penelitian ini memberikan bukti bahwa pendidikan berbasis agama dapat mendukung terwujudnya masyarakat yang lebih damai dan bersatu. Acts of racial discrimination in Indonesia are still relatively high and vulnerable. In the midst of cultural diversity and complex lifestyles, the potential for division is very vulnerable. Ethnic diversity in Indonesia presents two different things. On the one hand, we can see that with diversity, it becomes a source of cultural wealth and national identity. However, on the other hand, the existing cultural wealth can present a dilemma. The presence of diversity in our society has many influences on all aspects of community life that differ from one group to another. This fundamental difference can be seen in the interaction patterns they live in, when they dialogue with each other to convey messages or as a form of expression to fulfill their needs.  The existence of the Batak Tribe and the Sundanese Tribe, which are part of the majority community group, is a clear example of a community that has differences in speech intonation that must be considered in its delivery. We can see that the majority of Indonesian people consider that the Batak tribe is known as a group of people who have characters as brave, assertive, and like to speak in a loud tone. This situation is inversely proportional to the Sundanese tribe. Sundanese people are considered to have friendly, polite, and soft-spoken characters. These differences in characteristics often cause conflict or problems when communicating interpersonally. Through intercultural communication studies, it can solve the problem of hate speech in this study. Samovar, Poter and Daniel have intercultural communication concepts that can be a solution to the conflicts that often occur.  The result that can be found is that by recognising the context of intercultural communication that exists in heterogeneous societies, it is hoped that people will be able to accept cultural diversity, especially regarding hate speech. Another thing that can be produced, namely the existence of a bridge for the creation of knowledge exchange to understand the existence of other cultures that live outside their society.